A double-layer composite electrode based on SrSc0.2Co0.8O3-d perovskite with improved performance in intermediate temperature solid oxide fuel cells - An, B.; Guo, Y.; Ran, R.; Shao, Zongping (Elsevier Ltd, 2010)
Dual-layer composite electrodes consisting of a layer adjoining to an Sm0.2Ce0.8O1.9 (SDC) electrolyte composed of 70 wt.% SrSc0.2Co0.8O3-d + 30 wt.% Sm0.2Ce0.8O1.9 (SScC + SDC composite) and a second layer composed of 70 wt.% SrSc0.2Co0.8O3-d + 30 wt.% Sm0.5Sr0.5CoO3-d (SScC + SmSC composite) were fabricated and investigated as potential cathodes in intermediate temperature solid-oxide fuel cells. Thermo-mechanical compatibility between the two electrode layers and between the electrode and the electrolyte were examined by SEM, XRD and EIS. After sintering, no clear boundary between SScC + SDC and SScC + SmSC layers was observable by SEM. The repeated thermal cycling didn't induce the delamination of the electrode from the electrolyte nor the formation of cracks within the electrode. As a result, stable electrode performance was achieved during thermal cycling and long-term operation. Symmetric cell tests demonstrated that the dual-layer electrode with a ~10-µm SScC + SDC layer and a ~50-µm SScC + SmSC layer (SScC + SDC/SScC + SmSC (1:5)) had the lowest electrode-polarization resistance among those tested. Anode-supported fuel cells with an SDC electrolyte and SScC + SDC/SScC + SmSC (1:5) cathode were fabricated. Peak power density as high as 1326 mW cm-2 was achieved at 650 °C, which was higher than for similar fuel cells with a single-layer SScC + SDC or an SScC + SmSC composite electrode. © 2010 Professor T. Nejat Veziroglu.